Formaldehyde regulates tetrahydrofolate stability and thymidylate synthase catalysis. Issue 47 (17th May 2021) - Chen, Xiaolei; Chothia, Sara Y.; Basran, Jaswir; Hopkinson, Richard J.
Abstract : NMR studies on the formation and stability of 5, 10-methylenetetrahydrofolic acid reveal a non-enzymatic feedback mechanism mediated by formaldehyde. Abstract : Tetrahydrofolic acid and formaldehyde are key human metabolites but their physiologically relevant chemistry is undefined. Our NMR studies confirm formaldehyde as a product of tetrahydrofolic acid degradation but also reveal their reaction regulates the stability of tetrahydrofolic acid. These observations identify a novel non-enzymatic feedback mechanism regulating formaldehyde and folate metabolism that has important implications for folate-targeting chemotherapy in cancer and other diseases.